Corporate governance, financial constraints, and dividend policy: Evidence from Pakistan - M. Azeem; Nisar Ahmad; Safyan Majid; Jamshaid Ur Rehman; Bilal Nafees (Cogent Economics & Finance, 2023)
Information asymmetry between insiders and outsiders creates various issues for a firm, such as the agency problem where managers pursue their own interests even at the cost of the well-being of the firm's shareholders, and probable external financial constraints where external investors discount risk by causing a surge in the cost of financing. Normally, a firm manages the issues of the agency problem and external financing constraints by omitting or initiating dividend payments. Therefore, this study investigated the impact of corporate governance on dividend policies in the presence of financial constraints using a sample of 139 non-financial firms listed on PSE, where a weak regulatory framework generates agency problems and the underdevelopment of the financial sector causes financing constraints for businesses. The results reveal that, in Pakistan, dividends are an Outcome of governance practices. As the quality of firm-level governance improves, shareholders are provided with the legal strength to ultimately force firm managers to pay dividends. Along with the agency problem, the availability of external financing is an important factor related to dividend payment decisions in Pakistan. When a company is confronted with agency problems and financial constraints simultaneously, managers try to avoid costly external financing rather than reducing the agency's problem. The results of the study can be further refined by enhancing the study period and sample size. Furthermore, the work can be extended by classifying sample subjects to the nature of industry and group ownership.
Keywords: G34; G35; G0; 330; Corporate Governance; Dividend Policy; Financial Constraints